If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10h = 160 + -4h Solving 10h = 160 + -4h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '4h' to each side of the equation. 10h + 4h = 160 + -4h + 4h Combine like terms: 10h + 4h = 14h 14h = 160 + -4h + 4h Combine like terms: -4h + 4h = 0 14h = 160 + 0 14h = 160 Divide each side by '14'. h = 11.42857143 Simplifying h = 11.42857143
| 6+.14x=.29x | | 5(2n-3)=9(n+3) | | [6x-3]=21 | | 10n^5= | | 11n^2= | | t(1)=3+6n | | -n^2=74 | | 6-.12x=.48x | | n^2=1585 | | 3b-12b-15=0 | | X=-2-(-3) | | 7x+13y=-9 | | 4x-25=x+9 | | -3a^2=27 | | 53x=132.5 | | 3=5-5x/2 | | x+3(6+x)=20 | | 3x-2-2x=-10 | | 24=-2(b-30)+8 | | 2ln(X-3)-1=3 | | c=7n+40 | | 8(y+6)=30 | | y=2x^2-5x+18 | | 3x-y-10=0 | | .2=.9-.1x | | 8x+12-6x=8 | | 2x+4+3x+2=x+x-3 | | 12+8x+2=43-3x+4 | | 14x+3=-3x | | 6u-9=3u | | 3x-y-10=10 | | 6(-3m)4= |